Marketing en acquisitie voor ontwerpers : hoe het kan, hoe het wordt gedaan, hoe de klant het graag wil. - Preddy, Shan, ....- (Amsterdam : Bis, 2006)
The fast-paced nature of the design business means that you probably spend most of your time, energy and resources looking after your clients' needs, not your own. In our current, increasingly competitive marketplace where supply far outstrips demand, no design business will survive for long - let alone grow and develop - without a really effective marketing programme. It is no longer enough for you to provide a good product and simply hope for the best. Potential clients need to know exactly what you can do for them and what makes you different from your competitors. Existing clients need to know exactly why they should develop and continue their business with you. Quite simply, you need to convince design buyers that you are unequivocally the right consultancy for them, time and time again.
Keywords: Industrieel ontwerpen; Marketing